2022
DOI: 10.1161/circresaha.121.319412
|View full text |Cite|
|
Sign up to set email alerts
|

CircOGDH Is a Penumbra Biomarker and Therapeutic Target in Acute Ischemic Stroke

Abstract: Background: Acute ischemic stroke (AIS) is a leading cause of disability and mortality worldwide. Prediction of penumbra existence after AIS is crucial for making decision on reperfusion therapy. Yet a fast, inexpensive, simple, and noninvasive predictive biomarker for the poststroke penumbra with clinical translational potential is still lacking. We aim to investigate whether the CircOGDH (circular RNA derived from oxoglutarate dehydrogenase) is a potential biomarker for penumbra in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 56 publications
0
53
0
1
Order By: Relevance
“…The ectopic expression of miR-124 in the cortex promotes the differentiation of neural progenitor cells into neuronal lines, and further improves the anti-ischemic ability through cortical neurogenesis ( Zhou and Qi, 2021 ). Recent studies have reported that CircOGDH (cyclic RNA derived from ketoglutarate dehydrogenase) is highly expressed in plasma exosomes of patients with IS, and CircOGDH interacts with miR-5112 in primary cortical neurons to increase neuronal damage ( Liu Y. et al, 2022 ). By contrast, knockdown of CircOGDH significantly enhanced neuronal viability under ischemic conditions.…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ectopic expression of miR-124 in the cortex promotes the differentiation of neural progenitor cells into neuronal lines, and further improves the anti-ischemic ability through cortical neurogenesis ( Zhou and Qi, 2021 ). Recent studies have reported that CircOGDH (cyclic RNA derived from ketoglutarate dehydrogenase) is highly expressed in plasma exosomes of patients with IS, and CircOGDH interacts with miR-5112 in primary cortical neurons to increase neuronal damage ( Liu Y. et al, 2022 ). By contrast, knockdown of CircOGDH significantly enhanced neuronal viability under ischemic conditions.…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…By contrast, knockdown of CircOGDH significantly enhanced neuronal viability under ischemic conditions. Therefore, CircOGDH and miR-5112 may be potential therapeutic targets for regulating the viability of ischemic neurons ( Liu Y. et al, 2022 ).…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In animal and human experiments, they observed significantly increased expression of exosomal CircOGDH in the ischemic mouse primary cortical neurons and plasma of AIS patients, as compared to normoxic condition and noncerebrovascular disease controls, and the level of CircOGDH in the blood was positively correlated with the size of the penumbra tissue. Mechanistically, ischemic neuron-derived exosomes transported CircOGDH from the penumbra tissue to peripheral blood, and then upregulated COL4A4 (Gallus collagen, type VI, alpha VI) expression with sequestering of miR-5112, resulting in neuronal apoptosis [ 25 ]. Their study provided a potential intervention wherein knocking down CircOGDH could enhance neuronal cell viability in the ischemic penumbra tissue, contributing to improving neurological deficits in the acute phase of ischemic stroke.…”
Section: The Involvement Of Exosomal Noncoding Rnas In the Pathophysi...mentioning
confidence: 99%
“…In addition, exosomes can carry circRNA across the blood-brain barrier, allowing circRNA to exist stably in peripheral blood, making circRNA promising as a novel diagnostic and prognostic biomarker for IS ( 14 ). A recent study reported that CircOGDH expression was upregulated in the plasma of IS patients, and the CircOGDH expression was positively correlated with penumbra size ( 15 ). Li et al examined circulating blood circRNA expression profiles of acute stroke patients and healthy controls and identified differentially expressed circRNAs in IS patients ( 16 ).…”
Section: Introductionmentioning
confidence: 99%